2016
DOI: 10.1177/0883911516668666
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide-enriched poly(ε-caprolactone) electrospun nanocomposite scaffold for bone tissue engineering applications

Abstract: Tissue engineering aims at fabricating biological substitutes to improve, repair, and regenerate failing human tissues or organs. Designing a nanocomposite scaffolds with tailored properties that enhance the development of functional tissue can be an appropriate approach to achieve this purpose. In this study, the uniform and bead-free nanofibers of poly(ε-caprolactone) composited with different graphene oxide nanosheet contents (ranging from 0.5 to 2 wt%) were successfully fabricated through electrospinning p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 31 publications
4
45
0
Order By: Relevance
“…For example, the pure PCL scaffold had a tensile strength of 1.61 MPa, an elongation of 122%, and a Young’s modulus of 7.01 MPa. The addition of GO (2%) resulted in a considerable increase in tensile strength to 3.50 MPa, elongation to 131%, and Young’s modulus to 15.15 MPa [ 80 ].…”
Section: Graphene Family Materials Mediate Cells Into Osteogenic Diffmentioning
confidence: 99%
“…For example, the pure PCL scaffold had a tensile strength of 1.61 MPa, an elongation of 122%, and a Young’s modulus of 7.01 MPa. The addition of GO (2%) resulted in a considerable increase in tensile strength to 3.50 MPa, elongation to 131%, and Young’s modulus to 15.15 MPa [ 80 ].…”
Section: Graphene Family Materials Mediate Cells Into Osteogenic Diffmentioning
confidence: 99%
“…However, these methods had a significant role in the progress of the LTE field. 30,135 There are many methods used for TE approaches, including solvent-casting, [137][138][139][140] freeze-drying, 92,95,138,[141][142][143] electrospinning, [144][145][146][147] phase separation, 103,135 and gas foaming. 77 In this study, we represent some of these techniques that have been utilized in LTE.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Because of the excellent properties, graphene and its derivatives have been intensively studied for biomedical applications, such as drug delivery carriers, imaging agents, cancer photothermal therapy agents and tissue engineering scaffolds components. [24][25][26][27] Previous studies had indicated that the mechanical properties and biocompatibility of polymers bone scaffolds doped with GO were signicantly better than those of pure scaffolds. 28,29 Additionally, GO is composed of hydrophobic p domains in the core region and ionized groups along the edges.…”
Section: Introductionmentioning
confidence: 99%